MINAT PESERTA DIDIK TERHADAP EKSTRAKURIKULER SEPAK TAKRAW DI MAN 2 PONTIANAK - Almunajat, Almunajat; Supriatna, Eka; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine how much interest students have towards sepak takraw extracurricular in MAN 2 Pontianak. The research method used is quantitative descriptive with the form of survey research. The data source of this study is the students of class X and XI Pontianak 2 amounted to 551 respondents and the data used were questionnaires that have been validated. Based on the results of the research conducted, it can be concluded that the interest of sepak takraw extracurricular students includes as many as 14 respondents or 2.54%, interested in 330 respondents or 59.89%, 192 respondents or 34.84% enough. , the category of less interested as many as 15 respondents or 2.72%, and the category of very uninterested as many as 0 respondents or 0%. So the conclusion above states that there is a strong interest from MAN 2 Pontianak students for the formation of sepak takraw extracurricular as one of the sports that is competed in the Madrasyah Arts and Sports Competition (AKSIOMA) throughout Indonesia. Keywords: Interest, Students, Extracurricular, Sepak Takraw